Targeted Antitumor Mechanism of C-PC/CMC-CD55sp Nanospheres in HeLa Cervical Cancer Cells - Liu, Guoxiang; Xu, Xiaohui; Jiang, Liangqian; Ji, Huanhuan; Zhu, Feng; Jin, Bingnan; Han, Jingjing; Dong, Xiaolei; Yang, Fanghao; Li, Bing (Frontiers in Pharmacology, 2020)
In vitro studies have shown that C-Phycocyanin (C-PC) inhibited cervical cancer HeLa cells growth. We constructed C-PC/CMC-CD55sp nanospheres using C-PC, Carboxymethyl Chitosan (CMC), and CD55 ligand peptide (CD55sp) to allow for targeted anti-tumor effects against HeLa cells in vitro and in vivo. The characteristics of the nanospheres were determined using FTIR, electron microscopy, and laser particle size analysis. Flow cytometry, laser confocal microscopy and small animal imaging system showed the targeting of C-PC/CMC-CD55sp nanospheres on HeLa cells. Subsequently, the proliferation and apoptosis were analyzed by Cell Counting Kit-8 (CCK-8), flow cytometry, TUNEL assay and electron microscopy. The expression of the apoptosis-related protein was determined using western blot. The stainings of Hematoxylin and Eosin (HE) were employed to evaluate the cell condition of tumor tissue sections. The cytokines in the blood in tumor-bearing nude mice was determined using ELISA. These results showed that C-PC/CMC-CD55sp nanospheres were successfully constructed and targeted HeLa cells. The constructed nanospheres were more effective than C-PC alone in inhibiting the proliferation and inducing apoptosis in HeLa cells. We also found that C-PC/CMC-CD55sp nanospheres had a significant inhibitory effect on the expression of anti-apoptotic protein Bcl-2 and a promotion on the transformation of caspase 3 to cleaved caspase 3. C-PC/CMC-CD55sp nanospheres played an important role in tumor suppression, reduced the expression TGF-β, and increased IL-6 and TNF-α. This study demonstrates that the constructed new C-PC/CMC-CD55sp nanospheres exerted targeted anti-tumor effects in vivo and in vitro which provided a novel idea for application of C-PC, and provided experimental basis for comprehensive targeted treatment of tumors.